A Discourse Analysis of Teacher-Student Interaction in an EFL Classroom Based on FIACS at SMPN 1 Percut Sei Tuan - Jemima Indah Andayani; Alfira Khairunnisa Br Nadapdap; Nazwa Nur Rahmi; Nia Kristin Sianturi (Faculty of Tarbiyah nad Teacher Training, 2026)
This study aims to analyze the types of teacher–student interaction and to identify the factors influencing interaction patterns in an EFL classroom at SMP Negeri 1 Percut Sei Tuan. The research applied a descriptive qualitative method, focusing on classroom interaction between the teacher and students. The data were collected through classroom observation and video recording, then transcribed and analyzed using Flanders Interaction Analysis Categories (FIAC). The data analysis was conducted through data condensation, data display, and conclusion drawing. The findings reveal that classroom interaction is dominated by student response and teacher talk, including lecturing, giving directions, and asking questions. This indicates that students participate actively but mainly in a reactive manner. Furthermore, the interaction patterns are influenced by several factors, including the teacher’s teaching strategy, the type of classroom activities, students’ language proficiency and confidence, and the teacher-centered classroom environment, which limit students’ opportunities to initiate communication.